IMPACT OF AGRICULTURAL CREDIT ON PERFORMANCE OF RED CHILI FARMS IN INDONESIA - Silke Zorena Jono; Netti Tinaprilla; Feryanto Feryanto (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Limited capital is a common problem in small scale farming in Indonesia, and red chili farms is no exception. The red chili farmers require a certain amount of inputs to carry out production activities. High production costs of those inputs, however, has led farmers to reduce the use of the inputs. This results in low crop production, while the demand for red chili in Indonesia continues to increase. Credit is a form of financing that can be given to the farmers in order to raise their purchasing power for the required production inputs. Some studies show that there is a positive impact of credit on farms’ performance, while some other show the opposite results. The aim of this research is to examine the impact of credit on the performance of red chili farms in Indonesia. The method used in this research is propensity score matching. The result of this research revealed that credit has a positive and significant impact to the farm revenue. Meanwhile, the profits obtained by farmers who use credit ar not significantly different from those of farmers who do not use credit.